Room temperature ionic liquid promoted improved and rapid synthesis of 2,4,5-triaryl imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone - Siddiqui, S. A.; Narkhede, U. C.; Palimkar, S. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Tetrahedron, 2005)
An improved and rapid one-pot synthesis of 2,4,5-triaryl imidazoles in a room temperature ionic liquid is described, which does not need any added catalyst. Different ionic liquids based on 1-n-butyl and 1,3-di-n-butyl imidazolium salts were screened and their efficacy in terms of acidity and polarity have been correlated with yields and reaction period. The one-pot methodology resulting in excellent isolated yields in short reaction times is characterized by simple work up procedures and efficient recovery and recycling of the ionic liquid, which acts as a promoter. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 2-Diketones; 4; 5-triaryl imidazoles; alpha-hydroxyketone; ammonium acetate; benzaldehydes; ionic liquid (IL)

Antibacterial activity of synthesized 2,4,5-trisubstituted imidazole derivatives - Khan, Mohd Sajid; Siddiqui, Shafi Ahmad; Siddiqui, Mohammad Shaik Rafi Ahmad; Goswami, Usha; Srinivasan, Kumar Venkatraman; Khan, Mohammad Islam (Chemical Biology & Drug Design, 2008)
Some novel chemically synthesized 2,4,5-trisubstituted imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone were screened against eight different human pathogenic bacteria and fungi. Seven compounds were found to be active against different bacteria. These compounds showed variation in activity and were found to be active against Gram-positive as well as Gram-negative bacteria. Compound 4-(4,5-diphenyl-1H-imidazol-2-yl)-phenol, 3d was the only compound which showed activity against Klebsiella pneumoniae while rest of the compounds did not show significant activity against this micro-organism. Minimum inhibitory concentrations of the compounds were in the range of 0.50 to 6.1 mu g/mL and minimum bactericidal concentration ranges from 1.11 to 12.9 mu g/mL. The candidature of active compounds to be an effective and novel drug was examined based on Lipinski's rule of Five which explained ClogP, LogS, H-bond acceptors, H-Bond donors and rotational bonds. Compounds 3a-d and 3f satisfies Lipinski's rule of Five and could be proposed as potent new antibacterial drugs.
Keywords: 1; 2; 2-Diketones; 4; 5-trisubstituted imidazoles; alpha-hydroxyketone; antibacterial activity; aryl aldehydes

Efficient synthesis of quinoxalines in the ionic liquid 1-n-butylimidazolium tetrafluoroborate ([Hbim]BF4) at ambient temperature - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Quinoxaline derivatives have been synthesized in excellent yields using an ionic liquid (IL) (viz., 1-n-butylimidazolium tetrafluoroborate) as a reaction medium as well as promoter from various 1,2-diketones and aryl-1,2-diamines. The process is general for the synthesis of quinoxaline derivatives from aromatic as well as aliphatic-1,2-diketones. The advantages of the present method are ambient reaction temperature, simplicity of operation, high yields of products, the recyclability of the IL, and ecofriendly nature of the reaction medium.
Keywords: 1; 2-diamines; 2-Diketones; Aryl-1; ionicliquid(IL); quinoxalines

New synthetic route for 1,2-diketo compounds using unexpected C-C bond cleavage by PCC - Bhosale, Shrikar M.; Momin, Aadil A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient method has been established for the preparation of 1,2-diketones by unexpected C-C bond cleavage in 4-keto-2-hydroxy esters using pyridiniumchlorochromate (PCC). (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-Diketones; C-C bond cleavage; PCC

Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1